Object detection application and Viola Jones algorithm for the development of a database in Alzheimer's patients - Castillo Salazar, David (2019)
Alzheimer's, as well as other neurological diseases, alters progressively the communication abilities of people who suffer from it. In these cases, facial gestures are a very important means of communication and their treatment is the central objective of this investigation. This article describes the creation of a database with the information of patients with Alzheimer's disease represented on faces' images, respecting the etic and based on the normative and respective permissions, these care centers for the elderly people are located in different cantons of Ambato, Ecuador, which will be used later in investigations related to the recognition of facial gestures. It has worked with a population of 61 people diagnosed with Alzheimer's, between 69 and 98 years old. The data obtained on the images were processed using the Viola-Jones method, making it possible to detect objects quickly and accurately. This method used the algorithm of neighbors with the canny border's technique. As a result, it was possible to create a database that includes the images of the patients' faces, in a gray scale, using high resolution. This constitutes an important input for future research on the health subjects. It is concluded that the information obtained is of quality and pressure for future analysis.